High-purity nano aluminum oxide and preparation method thereof
Through a new process, the reaction of hydroxide and concentrated nitric acid is used to prepare high -purity nano alumina, which solves the problem of complex preparation process, low safety factor, and difficult quality control in existing technologies. Preparation of aluminum alumina with uniform particle size.
Patent Information
- Application Number
- CN202411624488.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the preparation process of nano alumina is complex, the safety factor is low, and the quality control is difficult.
By mixing and reacting aluminum hydroxide powder with concentrated nitric acid, an aluminum nitrate solution is obtained, which is then filtered and spray-dried to obtain aluminum nitrate powder. Subsequently, the aluminum nitrate powder is heated and dried to obtain a polymerized aluminum nitrate intermediate. After multiple filtrations, inorganic acid replacement and centrifugal separation, high-purity nano-alumina is finally obtained through flash drying and roasting.
Achieve the safety and simple preparation process of high -purity nanoxide, improve the purity and particle size uniformity of the product, reduce the impurities content, and solve the complex preparation process, low safety factor, difficult quality control in the existing technologies, difficulty in quality control. question.
Smart Images

Figure CN119349614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum oxide preparation, and in particular to high-purity nano aluminum oxide and a preparation method thereof. Background Art
[0002] The battery separator is the most important material in lithium-ion batteries. It isolates the positive and negative electrodes, preventing short circuits while allowing lithium ions to conduct through the electrolyte. During charging, lithium ions move from the negative electrode to the positive electrode through the separator. Conversely, during discharge, lithium ions move in the opposite direction. Commercial battery separator materials are made of organic polypropylene or polyethylene. Because of their poor temperature resistance, at high temperatures (above 65°C), the separator softens, causing short circuits, breakdown, and even spontaneous combustion. Alternatively, at low temperatures (below -10°C), the separator freezes, hindering lithium ion conduction and causing battery charging and discharging failure. Coating the surface of organic separators with ceramic powder is currently the most economical technology, which can improve the separator's high and low temperature resistance. Alumina has natural insulating and flame retardant properties and is currently the preferred choice for commercial separators. Alumina particle size and impurity content affect the function of the separator. For example, large-particle alumina coatings can be too thick, increasing weight and resistivity. The presence of other metal oxide impurities, such as iron, nickel, copper, and calcium, some of which are magnetic, can produce electromagnetic effects, affecting charge and discharge efficiency and even generating heat. Providing a high-purity nano-alumina material meets the current development needs of solid-state battery technology.
[0003] As early as 1975, Reynolds Metals Co applied for U.S. Patent No. 3,925,538, which disclosed a specific method for preparing aluminum nitrate crystals and polymerized aluminum nitrate (or basic aluminum nitrate) by reacting nitric acid and aluminum hydroxide. The method for preparing basic aluminum nitrate crystals in this patent can be summarized as follows: first, the aluminum nitrate crystals are heated to 180°C in a high-pressure device to remove the nitrate ions; second, the aluminum nitrate crystals from which the nitrate ions have been removed are diluted and mixed with water, and then heated again to 220°C. The solution is then filtered and dried to prepare polymerized aluminum nitrate powder.
[0004] US Pat. No. 4,256,714 describes a preparation method comprising using aluminum nitrate solution as an initial raw material and subjecting it to a steam pressure reaction at 27-450° C. to produce large-crystal polymerized aluminum nitrate.
[0005] The core of the preparation method of polyaluminum nitrate described in U.S. Patent No. 5,202,115 is to fully mix the aqueous solution of aluminum nitrate and metallic aluminum, then raise the temperature to directly generate a polyaluminum nitrate solution.
[0006] U.S. Patent No. 3,898,043 discloses a method for producing a polyaluminum nitrate solution by thermally decomposing a high-concentration aluminum nitrate solution. Other patents, such as U.S. Patent Nos. 4,223,000, 2,931,706, and 1,575,634, also propose similar methods for producing polyaluminum nitrate solutions using metallic aluminum. U.S. Patent No. 4,985,225 produces a polyaluminum nitrate solid by heating an aluminum nitrate solution.
[0007] The existing commonly used industrial production process of polymerized aluminum nitrate is usually in the following two directions: first, the reaction of metallic aluminum and aluminum nitrate; second, the reaction of metallic aluminum and dilute nitric acid. Both reactions require the use of metallic aluminum. In order to speed up the reaction rate, metallic aluminum needs to be processed into powder or aluminum chips and aluminum powder. At the same time, due to the reducing nature of metallic aluminum, some side reactions will occur. When metallic aluminum reacts with dilute nitric acid, hydrogen will be produced, which can easily cause the production equipment to explode, and thus the sealing and strength of the equipment are required to be high. The reaction between metallic aluminum and aluminum nitrate not only produces hydrogen, but also forms nitrogen oxides, thereby producing polluting gases. Strict tail gas treatment is also required, otherwise it will threaten atmospheric safety. The solutions produced by these two types are both acidic solutions, which are extremely difficult to transport, and the use of metallic aluminum as a raw material is also extremely difficult to control costs.
[0008] Numerous technologies have been developed both domestically and internationally for producing nano-alumina powders. The most typical route involves directly calcining aluminum hydroxide powder, followed by washing, drying, and pulverization. This technology presents several uncertainties. For example, the high sodium and other impurity content in alumina makes it difficult to remove impurities by washing the calcined powder. The levels of sodium and other impurities in the raw aluminum hydroxide fluctuate widely, making quality control difficult. The high hardness of calcined alumina makes it difficult to grind the powder to a uniform particle size and control its distribution. Summary of the Invention
[0009] The purpose of the present invention is to provide a high-purity nano-alumina and a preparation method thereof, so as to solve the technical problems of the prior art of nano-alumina, such as complex preparation process, low safety factor and difficult quality control.
[0010] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0011] The present invention provides a method for preparing high-purity nano-alumina, comprising the following steps:
[0012] Step 1): mixing aluminum hydroxide powder and concentrated nitric acid and reacting them to obtain an aluminum nitrate solution, which is then filtered and spray-dried to obtain aluminum nitrate powder;
[0013] Step 2): heating and drying the aluminum nitrate powder obtained in step 1) to obtain a polymerized aluminum nitrate intermediate;
[0014] Step 3): dispersing the polyaluminum nitrate intermediate obtained in step 2) in water to obtain a slurry, and then filtering, replacing with an inorganic acid, and filtering the slurry in sequence to obtain a filter cake;
[0015] Step 4): Re-dispersing the filter cake obtained in step 3) in water to obtain a slurry, and sequentially grinding and centrifuging the slurry to obtain a precipitate;
[0016] Step 5): The precipitate obtained in step 4) is flash dried and calcined to obtain high-purity nano-alumina.
[0017] Furthermore, in step 1), the reaction time is 0.5 to 5 hours, and the reaction temperature is 70 to 110° C.;
[0018] In the aluminum nitrate solution, the content of aluminum is 3-15 wt %, and the content of nitro groups is 10-30 wt %.
[0019] Furthermore, in step 1), the spray drying conditions are an inlet temperature of 120-200° C. and an outlet temperature of 40-60° C.;
[0020] The particle size of the aluminum nitrate powder is 20 to 150 μm.
[0021] Furthermore, in step 2), the heating and drying temperature is 110-250° C., and the heating and drying time is 0.5-3 h; the aluminum content of the polyaluminum nitrate intermediate is 10-40 wt %, the nitro content is 10-30 wt %, and the balance is water.
[0022] Furthermore, in step 3), the solid content of the slurry is 5-30%.
[0023] Furthermore, in step 3), the inorganic acid solution used in the inorganic acid replacement includes nitric acid solution, sulfuric acid solution or hydrochloric acid solution, and the mass concentration of the inorganic acid solution is 0.1 to 5%;
[0024] The molar ratio of the inorganic acid to the aluminum hydroxide in the inorganic acid solution is 3 to 5:1.
[0025] Furthermore, in step 4), the solid content of the slurry is 5 to 30%, and the particle size of the powder in the slurry obtained after grinding is 0.1 to 3 μm;
[0026] The centrifugal speed is 2000-4000 rpm.
[0027] Furthermore, in step 5), the flash drying conditions are: inlet temperature 150-350°C, outlet temperature 90-150°C.
[0028] Furthermore, in step 5), the calcination temperature is 300-1300° C., and the calcination time is 0.5-5 h.
[0029] The present invention also provides high-purity nano-alumina prepared by the above preparation method.
[0030] Beneficial effects of the present invention:
[0031] The preparation method of the present invention has a high safety factor and a simple process. The aluminum nitrate intermediate product is easy to prepare and can be dissolved in an aqueous phase for purification. It does not contain chloride ions and has low corrosion protection requirements for production equipment. After further roasting, nitrate ions are easily removed to obtain a high-purity alumina product. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the process flow of the present invention;
[0033] Figure 2 This is an electron microscope image of the sprayed aluminum nitrate solid powder prepared in Example 1;
[0034] Figure 3 This is an electron microscope image of the dry high-purity polyaluminum nitrate powder prepared in Example 1;
[0035] Figure 4 The XRD diffraction pattern of the high-purity alumina powder prepared in Example 1 is shown;
[0036] Figure 5 This is the XRD diffraction pattern of the high-purity alumina powder prepared in Example 6. DETAILED DESCRIPTION
[0037] The present invention provides a method for preparing high-purity nano-alumina, comprising the following steps:
[0038] Step 1): mixing aluminum hydroxide powder and concentrated nitric acid and reacting them to obtain an aluminum nitrate solution, which is then filtered and spray-dried to obtain aluminum nitrate powder;
[0039] Step 2): heating and drying the aluminum nitrate powder obtained in step 1) to obtain a polymerized aluminum nitrate intermediate;
[0040] Step 3): dispersing the polyaluminum nitrate intermediate obtained in step 2) in water to obtain a slurry, and then filtering, replacing with an inorganic acid, and filtering the slurry in sequence to obtain a filter cake;
[0041] Step 4): Re-dispersing the filter cake obtained in step 3) in water to obtain a slurry, and sequentially grinding and centrifuging the slurry to obtain a precipitate;
[0042] Step 5): The precipitate obtained in step 4) is flash dried and calcined to obtain high-purity nano-alumina.
[0043] In the present invention, the purity of the aluminum hydroxide powder is preferably: by mass fraction, the Al2O3 content is not less than 99%, the oxide impurity content is not more than 0.3%, and the silicon oxide content is not more than 0.4%.
[0044] In the present invention, in step 1), the reaction time is 0.5 to 5 hours, preferably 1 to 4 hours, more preferably 2 to 3 hours, more preferably 2.5 hours, and the reaction temperature is 70 to 110° C., preferably 80 to 100° C., more preferably 90° C.;
[0045] In the aluminum nitrate solution, the aluminum content is 3-15 wt%, preferably 5-12 wt%, more preferably 10 wt%, and the nitro content is 10-30 wt%, preferably 15-25 wt%, more preferably 20 wt%.
[0046] In the present invention, in step 1), the reaction formula of the aluminum hydroxide powder and concentrated nitric acid is:
[0047] Al(OH)3+3HNO3→Al(NO3)3+3H2O.
[0048] In the present invention, the pH of the aluminum nitrate solution is 0.5-5, preferably 1-3, and more preferably 2.
[0049] In the present invention, in step 1), the insoluble matter removed by filtration is mainly silicon oxide.
[0050] In the present invention, in step 1), the spray drying spray conditions are: inlet temperature 120-200°C, preferably 150-180°C, more preferably 170°C, outlet temperature 40-60°C, preferably 50°C;
[0051] The particle size of the aluminum nitrate powder is 20 to 150 μm, preferably 50 to 100 μm, and more preferably 80 μm.
[0052] In the present invention, the spray drying is carried out in a low-temperature spray machine, and the aluminum nitrate powder is round.
[0053] In the present invention, in step 2), the heating and drying temperature is 110 to 250° C., preferably 150 to 200° C., more preferably 180° C., and the heating and drying time is 0.5 to 3 h, preferably 1 to 2 h, more preferably 1.5 h; the aluminum content of the polymerized aluminum nitrate intermediate is 10 to 40 wt%, preferably 15 to 30 wt%, more preferably 20 wt%, the nitro content is 10 to 30 wt%, preferably 15 to 25 wt%, more preferably 20 wt%, and the balance is water.
[0054] In the present invention, in step 2), the purpose of the heating and drying is to remove part of the nitric acid, and it is preferably carried out in a vacuum oven with a vacuum degree of 0.02 to 0.08 mPa, preferably 0.05 mPa.
[0055] In the present invention, the reaction formula for heating and drying aluminum nitrate powder is: AlNO3·5H2O→Al2NO 3(6-n) +NO2+H2O, (n=1, 2, 3, 4, 5).
[0056] In the present invention, in step 3), the solid content of the slurry is 5 to 30%, preferably 10 to 25%, and more preferably 15%.
[0057] In the present invention, in step 3), the filter cake obtained after filtration is washed with water, and the mass ratio of water to filter cake is 1 to 5:1, preferably 2 to 4:1, and more preferably 3:1.
[0058] In the present invention, in step 3), the inorganic acid solution used in the inorganic acid replacement includes nitric acid solution, sulfuric acid solution or hydrochloric acid solution, preferably nitric acid solution or sulfuric acid solution, more preferably nitric acid solution;
[0059] The mass concentration of the inorganic acid solution is 0.1-5%, preferably 1-3%, and more preferably 2%;
[0060] The molar ratio of the inorganic acid to the aluminum hydroxide in the inorganic acid solution is 3 to 5:1, preferably 4:1.
[0061] In the present invention, the purpose of inorganic acid replacement is to remove impurity ions.
[0062] In the present invention, the inorganic acid replacement is followed by water washing until the pH value of the washing liquid reaches 7.
[0063] In the present invention, in step 4), the solid content of the slurry is 5-30%, preferably 10-25%, more preferably 15-20%, and more preferably 18%. The particle size of the powder in the slurry obtained after grinding is 0.1-3 μm, preferably 0.5-2.5 μm. More preferably, it is 1.5 μm.
[0064] The centrifugal speed is 2000-4000 rpm, preferably 2500-3500 rpm, and more preferably 3000 rpm.
[0065] In the present invention, the grinding is performed by a nano sand mill.
[0066] In the present invention, in step 5), the flash drying conditions are: inlet temperature 150-350°C, preferably 200-300°C, more preferably 250°C, outlet temperature 90-150°C, preferably 100-140°C, more preferably 120°C.
[0067] In the present invention, the flash drying is preferably carried out by placing the filter cake obtained after centrifugal separation in a flash evaporator, and the flash drying time is 2 to 5 seconds, preferably 3 seconds.
[0068] In the present invention, in step 5), the calcination temperature is 300-1300° C., preferably 500-1000° C., more preferably 800° C., and the calcination time is 0.5-5 h, preferably 1-4 h, more preferably 2-3 h, and more preferably 2.5 h.
[0069] In the present invention, calcination is carried out in a muffle furnace.
[0070] The present invention also provides high-purity nano-alumina prepared by the above preparation method.
[0071] In the present invention, the experimental instruments and materials are as follows: the spray dryer is Bayue BA-PWGZ1000B; the nano sand mill is Taiyi nano sand mill TYEE-0.3L; the flash evaporator is Qibao Drying XSG-2 laboratory flash evaporator; aluminum hydroxide was purchased from China Aluminum Shandong Aluminum Plant, brand HY1020-821, 65% solid content, and particle size 35 μm.
[0072] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0073] Example 1
[0074] 50.00 g of 65% concentrated nitric acid, 20.63 g of aluminum hydroxide powder, and 100 g of water were placed in a 2 L pressure reactor and reacted at 100° C. for 1 h. The mixture was then cooled, filtered, and the filtrate was collected. The filtrate was spray-dried at an inlet temperature of 160° C. and an outlet temperature of 50° C. The resulting aluminum nitrate powder with a particle size of 70 μm was collected and placed in an oven with a vacuum of 0.06 mPa and heated and dried at 180° C. for 1 h to obtain a polyaluminum nitrate intermediate. The polyaluminum nitrate intermediate was dispersed in water to obtain a slurry with a solid content of 20%. The slurry was filtered and washed with water five times to obtain a filter cake (the amount of water used for each wash was the same as the mass of the polyaluminum nitrate). The filter cake was redispersed in a 1% nitric acid solution (the molar ratio of nitric acid to aluminum hydroxide was 4.5:1) for inorganic acid replacement. After 1 h, the filtrate was repeatedly filtered and washed with water until the pH of the filtrate reached 7.
[0075] The obtained filter cake was redispersed in water to obtain a slurry with a solid content of 10%, which was ground until the particle size of the solid in the slurry was 1 μm. The slurry was collected and centrifuged at a speed of 3000 rpm to obtain a filter cake.
[0076] The obtained filter cake was flash dried for 3 seconds at an inlet temperature of 210°C and an outlet temperature of 100°C to obtain polymerized high-purity aluminum nitrate powder; the obtained powder was calcined at 550°C for 2 hours to obtain high-purity nano-alumina.
[0077] Example 2
[0078] Different from Example 1, in this example, the heating and drying temperature during the preparation of the polyaluminum nitrate intermediate is 250°C.
[0079] Example 3
[0080] Different from Example 1, in this example, the heating and drying time for preparing the polyaluminum nitrate intermediate is 3 hours.
[0081] Example 4
[0082] Different from Example 1, in this example, hydrochloric acid with a mass concentration of 1% is used during the inorganic acid replacement.
[0083] Example 5
[0084] Different from Example 1, in this example, after the slurry is ground, the solid particle size is 0.4 μm.
[0085] Example 6
[0086] Different from Example 1, in this example, the calcination temperature of the polymerized high-purity aluminum nitrate powder is 1200°C.
[0087] Comparative Example 1
[0088] Aluminum hydroxide powder and water are mixed in a mass ratio of 1:5 to obtain a slurry with a solid content of 20%, which is then filtered. The resulting filter cake is mixed with a nitric acid solution with a mass concentration of 2% (the molar ratio of nitric acid to aluminum hydroxide in the nitric acid solution is 4.5:1) to obtain a slurry with a solid content of 20%. The mixture is allowed to stand at room temperature for 1 hour and then centrifuged. The resulting filter cake is repeatedly washed with water until the pH of the filtrate is neutral, and then redispersed with water to obtain a slurry with a solid content of 15%. The mixture is ground and centrifuged. The resulting filter cake is flash dried for 3 seconds, then calcined at 1200°C for 2 hours, cooled, and subjected to air flow milling to obtain aluminum oxide powder with a particle size of 1.5 μm.
[0089] Table 1 shows the physical and chemical property parameters of the aluminum oxide powders obtained in Examples 1 to 6 and Comparative Example 1.
[0090]
[0091] It can be seen from the above embodiments that the present invention provides a high-purity nano-alumina and a preparation method thereof. Figure 1 It is a schematic diagram of the process flow of the present invention; Figure 2 This is an electron microscope image of the sprayed aluminum nitrate solid powder prepared in Example 1; Figure 3 This is an electron microscope image of the high-purity polyaluminum nitrate powder obtained by grinding and drying the slurry prepared in Example 1; Figure 4 This is the XRD diffraction pattern of the high-purity Gamma alumina powder prepared in Example 1; Figure 5 This is the XRD diffraction pattern of the high-purity Alfa alumina powder prepared in Example 6. As can be seen from the figure, the high-purity nano-alumina particles of the present invention are uniform, with a pure crystal phase after calcination and a narrow particle size distribution. Products with different crystal phases can be produced according to different processes to meet various customer needs. This shows that the present invention has a simple preparation process and a high safety factor. The resulting nano-alumina has high purity, uniform particle size, and low impurity content, resolving the technical problems of the prior art nano-alumina, which suffer from complex preparation processes, low safety factors, and difficult quality control.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing high-purity nano-alumina, characterized in that: The following steps are involved: Step 1): mixing aluminum hydroxide powder and concentrated nitric acid and reacting them to obtain an aluminum nitrate solution, followed by filtering and spray drying to obtain aluminum nitrate powder; Step 2): heating and drying the aluminum nitrate powder obtained in step 1) to obtain a polymerized aluminum nitrate intermediate; Step 3): dispersing the polymerized aluminum nitrate intermediate obtained in step 2) in water to obtain a slurry, and then filtering, replacing with an inorganic acid, and filtering the slurry in sequence to obtain a filter cake; Step 4): the filter cake obtained in step 3) is redispersed in water to obtain a slurry, and the slurry is successively ground and centrifuged to obtain a precipitate; Step 5): The precipitate obtained in step 4) is flash dried and calcined to obtain high-purity nano-alumina.
2. The method for preparing high-purity nano-alumina according to claim 1, characterized in that: In step 1), the reaction time is 0.5 to 5 hours, and the reaction temperature is 70 to 110° C.; In the aluminum nitrate solution, the content of aluminum is 3-15 wt %, and the content of nitro is 10-30 wt %.
3. The method for preparing high-purity nano-alumina according to claim 1 or 2, characterized in that: In step 1), the spray drying conditions are as follows: an inlet temperature of 120 to 200° C. and an outlet temperature of 40 to 60° C.; The particle size of the aluminum nitrate powder is 20 to 150 μm.
4. The method for preparing high-purity nano-alumina according to claim 3, characterized in that: In step 2), the heating and drying temperature is 110-250° C., and the heating and drying time is 0.5-3 h; the aluminum content of the polyaluminum nitrate intermediate is 10-40wt%, the nitro content is 10-30wt%, and the balance is water.
5. The method for preparing high-purity nano-alumina according to claim 4, characterized in that: In step 3), the solid content of the slurry is 5 to 30%.
6. The method for preparing high-purity nano-alumina according to claim 1, 4 or 5, characterized in that: In step 3), in the inorganic acid replacement, the inorganic acid solution used includes nitric acid solution, sulfuric acid solution or hydrochloric acid solution, and the mass concentration of the inorganic acid solution is 0.1-5%; The molar ratio of the inorganic acid to aluminum hydroxide in the inorganic acid solution is 3 to 5:
1.
7. The method for preparing high-purity nano-alumina according to claim 6, characterized in that: In step 4), the solid content of the slurry is 5-30%, and the particle size of the powder in the slurry obtained after grinding is 0.1-3 μm; The centrifugal rotation speed is 2000-4000 rpm.
8. The method for preparing high-purity nano-alumina according to claim 7, characterized in that: In step 5), the flash drying conditions are: inlet temperature 150-350°C, outlet temperature 90-150°C.
9. The method for preparing high-purity nano-alumina according to claim 7 or 8, characterized in that: In step 5), the calcination temperature is 300-1300° C. and the calcination time is 0.5-5 h.
10. High-purity nano-alumina prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Process of purifying aluminum nitrate
US1575634A
Preparation of dibasic aluminum nitrate
US2931706A
Apparatus for decomposing concentrated aqueous aluminum nitrate solutions
US3898043A
Process for producing alumina monohydrate from basic aluminum nitrates
US3925538A
Decomposition of aluminum nitrate
US4223000A